Phenolic content, anti-oxidative, anti-α-amylase and anti-α-glucosidase activities of Solanum diphyllum L. - Hossain, Sheikh Julfikar; El-Sayed, Magdi A; Mohamed, Aboul-Hamid H; Sheded, Mohamed G; Aoshima, Hitoshi (Bangladesh Journal of Botany, 2010)
Total phenolic content, anti-oxidative, anti-α-amylase and anti-α-glucosidase activities in the powder extracts of fruits, leaves, roots and stems of Solanum diphyllum were determined. Leaf extract had the highest total polyphenol content (68.1 mg GAE/g), followed by stems (48.6 mg GAE/g), fruits (38 mg GAE/g) and roots (26 mg GAE/g). By employing different assays such as DPPH radical scavenging, reducing power, Fe2+ chelating and total anti-oxidant capacity, it was found that leaf and stem extracts had promising anti-oxidative activity. Stem extract had highest level of α-amylase and α-glucosidase inhibition at concentrations of 1.0 and 0.5 mg/ml, respectively. Key words: Anti-oxidant; Anti-α-amylase; Anti-α-glucosidase; Polyphenol; Solanum diphyllum DOI: 10.3329/bjb.v38i2.5138 Bangladesh J. Bot. 38(2): 139-143, 2009 (December)